OPTIMIZING THE PRE-HOSPITAL MOBILE CARE SYSTEM: A CASE STUDY - CORDEIRO, Dirac Moutinho; CORDEIRO, Gauss Moutinho; CUNHA, Daniel José Dias (Brazilian Journal of Biometrics, 2018)
Freidenfields (1980) introduced for the modeling of several transport systems demands the concepts of queueing theories and studied the problem of the capacity expansion of the transport system as a random process of life and death, showing that it is possible to adapt the stochastic model of demand growth into a deterministic model. Souza (1996) applied this theory to predict the expansion of the emergency care systems. The modeling of the supply of Us integrated into the hospitals - emergency care and inter-hospital removals - despite being considered a restricted market service, as new solutions are developed new knowledge is aggregated into an increasingly lower cost (GOLDBERG, 2004). The dimensioning, allocation and distribution of the supply of Us developed for the pre-hospital mobile care system, utilizing data based on the Brazilian situation, is a field that deserves extreme attention. That will allow the assessment of the present situation and can lead to new routes in terms of public policies. Thus, the distribution of service stations of the regulation centers represents the ordering and orienting element of the State Systems of Urgency and Emergency. These centers must be structured in all levels, organizing the relation between several services, qualifying the flux of patients in the system and generating an integrative gateway for the hospitals, by which distress signals are received, evaluated and ranked. These rules must be followed by all services, both public or private. It can be mentioned, as an example, that for the emergency services a widely used measure is the maximization use of the Us or the minimization of response time TR, between any user of the transport system and the nearest hospital.